Detection of virulence genes of APEC (avian pathogenic Escherichia coli) isolated from poultry in Noakhali, Bangladesh - Hossain, Farzana Ehetasum; Islam, Saiful; Islam, Md Aminul; Islam, Shariful; Ahmed, Firoz (Bioresearch Communications, 2021)
Avian colibacillosis, caused by avian pathogenic Escherichia coli (APEC), is one of the major infectious diseases of poultry that bring about great economic loss for the Bangladesh poultry industry. The present study aimed to determine the virulence genes of avian pathogenic Escherichia coli (APEC) from cases of colibacillosis in poultry at the Noakhali district of Bangladesh. Currently, virulence-associated gene profiles of APEC isolates were investigated by polymerase chain reaction (PCR). A total of 24 (twenty-four) Escherichia coli isolates were collected and presumptively identified from 8 (eight) colibacillosis cases from 4 commercial broiler poultry farms (2 broilers per farm) in Noakhali, Bangladesh. The pathogenesis of Escherichia coli involves a wide range of different virulence genes. At this point, four virulence genes, iutA, hlyF, iroN, and iss were detected by PCR analysis. It has been observed that iutA, iss, hlyF, and iroN genes were found in 7(29.16%), 20(83.33%), 22(91.66%), and 24(100%) APEC isolates respectively. Furthermore, out of the twenty-four APEC isolates, six (25%) isolates had four virulence genes, fourteen (58.33%) isolates carried at least three virulence genes, three (12.5%) isolates carried two genes and one (4.16%) isolates had one virulence gene. Most importantly. six types of virulence gene profiles existed within the APEC isolates from which profile number 3 (hlyF, iroN, iss) having 13 (54.16%) isolates were predominant. The occurrence of APEC isolates of this region which is responsible for avian colibacillosis cases can be a matter of concern from the public health point of view. Future investigations will be able to utilize these virulence genes to identify APEC in Bangladesh helping in the diagnosis and prevention of colibacillosis in poultry. Bioresearch Commu. 7(1): 967-972, 2021 (January)